Synthesis of isomeric corniculatolides - Raut, Gajanan N.; Chakraborty, Kasturi; Verma, Priyanka; Gokhale, Rajesh S.; Reddy, D. Srinivasa (Tetrahedron Letters, 2012)
Synthesis of three natural macrolides 11-O-methylcorniculatolide A, 11-O-methylisocorniculatolide A and isocorniculatolide A is reported using a simple, straight forward and high-yielding route. The present synthesis confirms the assigned molecular structures and provides an access to sufficient quantities of the natural products for the biological evaluation. In addition, we have determined the anti-TB potential of the three natural compounds using Alamar-Blue assay (H(37)Rv) and found no significant inhibitory activity at 100 mu g/ml. Excellent yields, short sequence and useful SAR information are the highlights of the present work. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Diaryl ether; Isocorniculatolide; Macrocyclization; Mitsunobu reaction; Total synthesis

Synthesis, biological evaluation and docking studies of silicon incorporated diarylpyrroles as MmpL3 inhibitors: an effective strategy towards development of potent anti-tubercular agents - Vasudevan, N.; Motiwala, Zenia; Ramesh, Remya; Wagh, Sachin B.; Shingare, Rahul D.; Katte, Revansiddha; Anand, Amitesh; Choudhary, Sushil; Kumar, Ajay; Gokhale, Rajesh S.; Kulkarni, Kiran A.; Reddy, D. Srinivasa (European Journal of Medicinal Chemistry, 2023)
Growing global demand for new molecules to treat tuberculosis has created an urgent need to develop novel strategies to combat the menace. BM212 related compounds were found to be potent anti-TB agents and they inhibit mycolic acid transporter, MmpL3, a known potent drug target from Mycobacterium tuberculosis. In order to enhance their inhibitory potency, several silicon analogues of diarylpyrroles related to BM212 were designed, synthesized, and evaluated for anti-tubercular activities. In Alamar blue assay, most of the silicon-incorporated compounds were found to be more potent than the parent compound (BM212), against Mycobacterium tuberculosis (MIC = 1.7 & mu;M, H37Rv). Docking results from the crystal structure of MmpL3 and silicon analogues as pharmacophore model also strongly correlate with the biological assays and suggest that the incorporation of silicon in the inhibitor scaffold could enhance their potency by stabilizing the hydrophobic residues at the binding pocket. The best docking hit, compound 12 showed an MIC of 0.1 & mu;M against H37Rv with an acceptable in vitro ADME profile and excellent selectivity index. Overall, the present study indicates that, the designed silicon analogues, especially compound 12 could be a good inhibitor for an intrinsically flexible drug-binding pocket of MmpL3 and has potential for further development as anti-tubercular agents.
Keywords: antibiotic; BM212; docking studies; MmpL3 inhibitor; Silicon analogue; tuberculosis